JMP®, JMP IN® , and JMP Serve ™ - C.H. Spiegelman (Chemometrics and Intelligent Laboratory Systems, 1991)
The ethical issue of conscience rights is a conflict of at least two values: the autonomy of the physician and the autonomy of the patient. The task of commentators is to circumscribe the right to refuse (for the clinician) and the right to request (of the patient) in a way that preserves a healthy pluralism. In arguing for circumscribing each right, one risks assuming a moral claim ab initio, thus the arguments for circumscription are circular. This article argues on non-circular grounds for a wide tolerance for conscientious objections. Argued here is that given philosophical naturalism and evolutionary theory, one should be skeptical of moral claims, especially claims of the sort that one ought to do such and such. If the argument presented here is valid and sound, bioethicists (at least secular ones) should be more skeptical of what one is obligated to do. And that includes being skeptical about what others are obligated to do.